Halogen bonding in 2,5-dichloro-1,4-benzoquinone: insights from experimental and theoretical charge density analysis - Hathwar, Venkatesha R.; Gonnade, Rajesh G.; Munshi, Parthapratim; Bhadbhade, Mohan M.; Row, Tayur N. Guru (Crystal Growth & Design, 2011)
Experimental charge density distribution in 2, 5-dichloro-1, 4-benzoquinone has been carried out using high resolution X-ray diffraction data at 90 K to quantitatively evaluate the nature of C-Cl center dot center dot center dot O=C halogen bond in molecular crystals. Additionally, the halogen bond is studied from geometrical point of view and the same has been visualized using Hirshfeld surface analysis. The obtained results from experimental charge density analysis are compared with periodic quantum calculations using B3LYP 6-31G(d,p) level of theory. The topological values at bond critical point, three-dimensional static deformation density features and electrostatic potential isosurfaces unequivocally establish the attractive nature of C-Cl center dot center dot center dot O=C halogen bond in crystalline lattice.